Current options for aromaphytotherapy in the treatment of acute respiratory infections in children - O. M. Konova; I. V. Davydova; E. G. Dmitrienko; T. V. Turti; M. I. Ivardava (Медицинский совет, 2014)
Acute infectious respiratory diseases are among the most common childhood pathologies in the structure of medical aid appealability. A child typically suffers from 2 to 5-6 episodes of ARI during the year, which are often complicated by bronchitis, pneumonia or ENT diseases. Medication treatment recommended by the doctor does not always result in full recovery, and leads to certain side effects. Aromaphytotherapy is one of the major symptomatic treatments for respiratory diseases in children, which in many cases allows to significantly reduce the pharmacotherapeutic burden on the child's organism. The crucial task for today is to develop innovative standardized medicines for aromaphytotherapy with proven efficacy and safety in children, and easy to administrate formulations.